2014
DOI: 10.2147/nss.s55538
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor sleep quality among Lebanese university students: association between evening typology, lifestyle behaviors, and sleep habits

Abstract: Adequate, good night sleep is fundamental to well-being and is known to be influenced by myriad biological and environmental factors. Given the unavailability of sleep data about Lebanon, the cultural shifts and socioeconomic pressures that have affected many aspects of society, particularly for students and working adults, as well as our understanding of sleep in university students in other countries, we conducted a national study to assess sleep quality and factors contributing to sleep and general health i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
68
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 56 publications
19
68
2
3
Order By: Relevance
“…The percentages of good/poor sleepers found in sample 2 according to the PSQI and the mean overall PSQI score (see instruments section) were similar but systematically lower compared to those reported in many other studies with university student samples (Carney et al, 2006;Cheng et al, 2011;Clegg-Kraynok et al, 2011;Kabrita et al, 2014;Lemma et al, 2012Lemma et al, , 2013Lund et al, 2010). This suggests that sample 2 does not over represent poor sleepers, so it is not biased in in this sense.…”
Section: Methodssupporting
confidence: 64%
“…The percentages of good/poor sleepers found in sample 2 according to the PSQI and the mean overall PSQI score (see instruments section) were similar but systematically lower compared to those reported in many other studies with university student samples (Carney et al, 2006;Cheng et al, 2011;Clegg-Kraynok et al, 2011;Kabrita et al, 2014;Lemma et al, 2012Lemma et al, , 2013Lund et al, 2010). This suggests that sample 2 does not over represent poor sleepers, so it is not biased in in this sense.…”
Section: Methodssupporting
confidence: 64%
“…The pooled mean sleep duration was 7.08 h/d, which is within the range (6.4-7.9 h/d) reported in other countries. [39][40][41][42] The variation between different studies could be partly attributed to the discrepancy in socioeconomic and cultural factors, sampling methods, and measurements. Although the mean sleep duration was within the standard recommended range of 7 to 9 h/d, 34 the proportion of students with less than 6 hours sleep duration was 8.4%, which is higher than the corresponding The proportion of students with sleep duration less than 7 h/d was 41.3% (95% CI: 35.0% to 47.9%), which is higher than the corresponding figure (33.4%) in a study in Chinese adults.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that academic efficiency diminishes with increased excessive daytime sleepiness (OR = 0.86, 95% CI= 0.75 and 0.98). Kabrita et al [37] have investigated sleep quality on 540 students in state and private universities in Lebanon. Mean night sleep has been found as 7.95 ± 1.34.…”
Section: Discussionmentioning
confidence: 99%